Indigenous peoples’ food systems: Insights on sustainability and resilience in the front line of climate change - Food and Agriculture Organization of the United Nations; Alliance of Bioversity International and CIAT (Food and Agriculture Organization of the United Nations, 2021)
This book acknowledges the contributions that indigenous peoples’ food systems and indigenous peoples can make to achieving the Sustainable Development Goals (SDGs) by 2030 and brings to the attention of researchers and policymakers the need to have these indigenous food systems taken into consideration in the ongoing discussions about the transformation of the food systems to more sustainable, efficient and nutritious systems. The participatory research highlights the significant heterogeneity and richness of indigenous peoples’ food systems, which offer unique territorial management techniques that preserve biodiversity, while providing foods, livelihoods, nutrition, and byproducts for indigenous communities. The indigenous communities represented in the book are: The Baka (Cameroon); The Inari Sámi (Finland); The Khasi (India); The Melanesians (Solomon Islands); The Kel Tamasheq (Mali); The Bhotia and The Anwal (India); The Tikuna, The Cocama, and The Yagua (Colombia); and The Maya Ch’orti’ (Guatemala). The eight food system profiled in this book, reflect the depth of the discussions with the participating communities, highlighting their concerns, threats and unique practices, many at risk of disappearing. The research confirms the need for more systemized research on these food systems.